The Influence of The Student Teams Achievement Divisions (STAD) Cooperative Learning Model on Class III Student Learning Outcomes Theme 1 Subtheme 1 at UPTD SD Negeri 125543 Pematang Siantar - Meylan Hanna Sitinjak; Theresia Siahaan; Hetdy Sitio (MultiTech Publisher, 2023)
The Student Teams Acvhiement Divisions (STAD) type cooperative learning model on the learning outcomes of class III Theme 1 Subtheme 1 students at UPTD SD Negeri 125543 Pematang Siantar. The research method used is Quantitative with Pre-Experimental Designs research type and One-Group Pretest-Posttest research design. The research population was class III UPTD SD Negeri 125543 Pematang Siantar as many as 23 people. The data collection technique is in the form of a pretest and posttest . By carrying out the pretest stage , providing treatment by applying the Student Team Acvhiement Divisions (STAD) type cooperative learning model and posttest , research data was produced. The average pretest result was 61.09 which was included in the poor category or did not meet the KKM, then the average posttest result was 76.09 which was included in the good category. Based on the results of data analysis and the hypotheses tested, it is known that the Student Teams Acvhiement Divisions (STAD) type cooperative learning model has an effect on student learning outcomes. This is proven by the results of the t test with the paired sample t-test statistical test type, the value obtained is 6.617. With a frequency (db) of 23 — 1 = 22, at the significance level = 0.05 , it is obtained , namely 2.074. So it is obtained > or 6.617 > 2.074 then H 0 is rejected and Ha a is accepted, which means that the hypothesis in this study Ha a is accepted. Thus, the cooperative learning model of the Student Teams Acvhiement Divisions (STAD) type influences the learning outcomes of class III Theme 1 Subtheme 1 students at UPTD SD Negeri 125543 Pematang Siantar.